Lean and BIM Interaction in a High Rise Building - Chuquín, Frank (2021)
Lean Design has been spreading its use in the AEC industry along with the emergence of Building Information Modelling (BIM).Those two methodologies; Lean and BIM are being implemented first independently and then together. as new means to deliver more efficient projects. This paper researches some tools of Lean and BIM that permit a positive interaction by focusing on a case study related to a high rise building for residential use. Those tools are; from Lean Construction, set based design and value stream mapping. From BIM were used a 3D model and Integrated Concurrent Engineering (ICE) sessions. Also, the paper describes the interaction between those tools in the design phase and its impact in the construction stage.